Recent Advancements and Applications of Phospholipid Complexes: A Strategy to Enhancing the Bioavailability of Phytopharmaceuticals - Gaur, Praveen K.; Singh, Rashmi; Rastogi, Sameer; Lata, Kanak (Drug Delivery Letters, 2023)
Phytopharmaceuticals are herbal medicines that include standardized extracts, bioactive fractions, and purified phytoconstituents. They have been used for the cure, treatment, and mitigation of diseases since ancient times. Phytopharmaceuticals have a wide array of health benefits but their therapeutic efficacy is limited due to poor absorption, low bioavailability, and early elimination profile. A novel phospholipid complex is a newly introduced patented technology initially developed to incorporate standardized plant extracts/fractions or water-soluble phytoconstituents into phospholipids to produce a lipid compatible molecular complex, called phytosome, which improves their absorption and bioavailability. In herbal formulations, phytosome is the most advanced dosage form that has upgraded absorption rate and improved pharmacokinetics in comparison with conventional products. Phospholipid-complex is the result of hydrogen bonding between phospholipids and phytoconstituents, which offers maximum incorporation of herbal active ingredients into the lipidic layer and core. The increased therapeutic efficacy is due to the formation of amphiphilic phospholipid complex of herbal medicine. This review highlights the role of phospholipids in the delivery of herbal bioactives and natural extracts with special emphasis on phytosomes. Moreover, the current status of bioavailabilities, commercial products, patents, and clinical trials of phytosomal system of phytopharmaceuticals were addressed.
Keywords: clinical trials